CIM systems an introduction to computer-integrated manufacturing - Mitchell, F.H. (Ferdinand Haverman) 1938- (Prentice Hall, 1991)
Combining manufacturing systems with management techniques, this integrated approach to designing and developing CIM systems provides a multi-disciplinary, system-oriented background understanding of advanced manufacturing issues and strategies. It also offers design methods that can be used to create competitive manufacturing systems. The text's methods include assessing problems, determining solution approaches and developing and integrating systems based on relevant engineering, science and management disciplines. Software is included for a simple system-environment simulation (SES) model that illustrates the application of key concepts. Real-world application design models are applied to specific system examples. The author discusses design principles within a comprehensive framework, providing a context for understanding manufacturing operations and relationships. Throughout the text, the integrated technical and management considerations aim to encourage effective CIM team management.